External training load dynamic during short-term and long-term periods in an elite football team - Cavaca, M. L.; Valamatos, M. J.; Carita, A. I.; Marques, T.; Pinho, G. R.; Fatela, P. (Sport Sciences for Health, 2025)
The external training load represents a fundamental asset to control the physiological demands of training and competition scenarios. Specifically, to maximize players´ performance at match day, in each training session, coaches may define goals to be achieved in external load´s variables. The analysis and understanding of external load dynamics can be particularly important due to the different demands determined by the micro-cycle day. Thus, in this study, we aim to understand the external load dynamic, performed by elite male football players (age:19.9 ± 1.39 years), in short-term periods (i.e., inside each micro-cycle), and in a long-term period (i.e., twenty-three microcycles). For those purposes, we collected external load data from each player, during trainings and matches, for a period of twenty-three weeks, using portable GPS devices. External load was analyzed considering total distance (TD), high-speed running (HSR), sprint distance (SpD), number of sprints (SpN), meterage per minute (m.min), number of accelerations (ACC) and decelerations (DCC), and the sum of accelerations and decelerations (ACC + DCC). The results showed that during the week, MD-3 was the session with higher physical demands, and that MD-1 was the less physically demanding session. Moreover, training was concurrent at MD-3, with the higher weekly values for endurance (i.e., TD and HSRD) and strength workload (i.e., ACC + DCC) variables, with elevated effect size values (generally d > 1). Additionally, weekly workload represented an overload of the match demands, where ACC + DCC is highly impacted than any of the running efforts (i.e., TD, HSRD and SpD). For running variables, the higher the intensity, the lower the overload during the micro-cycle.